2021
DOI: 10.3389/fonc.2021.787864
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of PD-L1 Expression In Patients With Primary Oropharyngeal Squamous Cell Carcinoma: A Meta-Analysis

Abstract: BackgroundAt present, the prognostic significance of programmed cell death receptor ligand 1 (PD-L1) expression in oropharyngeal squamous cell carcinoma (OPSCC) patients is still controversial. In this study, we aim to synthesize relevant studies that have assessed the prognostic value of PD-L1 in patients with primary OPSCC treated according to the current standard-of-care.MethodsA systematic search of Medline/PubMed, Cochrane, Embase, Web of Science, and Scopus was conducted to define the prognostic role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…In another study, only high PD-L1 expression on immune cells but not on tumor cells was found to correspond with superior survival in HNSCC patients receiving surgery [ 29 ]. A recent meta-analysis showed favorable outcomes regarding increased tumoral PD-L1 expression in oropharyngeal cancer patients, both after surgery and primary (chemo)radiotherapy [ 27 ]. In line with the result of this meta-analysis, our study (in which more than 40% of patients suffered from oropharyngeal cancer) showed favorable LRC rates in patients with positive TPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, only high PD-L1 expression on immune cells but not on tumor cells was found to correspond with superior survival in HNSCC patients receiving surgery [ 29 ]. A recent meta-analysis showed favorable outcomes regarding increased tumoral PD-L1 expression in oropharyngeal cancer patients, both after surgery and primary (chemo)radiotherapy [ 27 ]. In line with the result of this meta-analysis, our study (in which more than 40% of patients suffered from oropharyngeal cancer) showed favorable LRC rates in patients with positive TPS.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting data regarding the prognostic value of tumoral PD-L1 expression in HNSCC [24][25][26][27][28][29][30][31]. Within a multicenter study of the German Cancer Consortium Radiation Oncology Group, Balermpas et al showed a positive relationship between elevated PD-L1 expression and survival in locally advanced HNSCC patients treated by postoperative chemoradiotherapy [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomarkers associated with the immune compartment of the tumor microenvironment (TME) have shown prognostic value in HPV + TC. For instance, several studies have highlighted a correlation between tumor-infiltrating CD8 + T-cells, T regulatory cells (Tregs) ( 5 , 6 ), and PD-L1 expression ( 7 , 8 ), respectively, to clinical outcome. However, immune-checkpoint blockade strategies, aiming at inducing T-cell responses, have shown limited clinical efficacy in HNCs, irrespective of HPV status ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, PD-L1 is not only a guidance for the use of immune checkpoint inhibitors (ICIs) (7), but also a potential prognostic indicator for head and neck cancer. Although studies on the prognosis of PD-L1 expression in head and neck cancer emerge one after another, the conclusions are controversial, and even the conclusions of some meta-analyses including large sample data are inconsistent (8)(9)(10)(11)(12)(13)(14). Meanwhile, PD-L2 is another important receptor of PD-1, and its binding affinity to PD-1 is about 2-6 times higher than that of PD-L1 (15).…”
Section: Introductionmentioning
confidence: 99%